COVID-19: WAR OF METAPHORS THE COVERAGE OF NOVEL CORONAVIRUS PANDEMIC IN GEORGIAN NEWS REPORTS - Iritspukhova, Nazi (Online Journal of Humanities ETAGTSU, 2020)
The paper uses the concepts of metaphor scenarios (Musolff, 2006; 2016) and discourse metaphors (Zinken et al, 2008) to analyze media discourses, specifically those of news reports, about COVID-19 (Novel coronavirus) situation in Georgia. The time span runs from the first confirmed case of COVID19 in Georgia, i.e. February 26th, till mid-May. The methodology also relies on earlier studies of infections and other diseases such as SARS, avian/bird flu, ZIKA, Foot and Mouth Disease, AID/HIV, cancer, etc. For identifying metaphorical linguistic expressions, the combination of Metaphor Identification Procedure /MIP (Pragglejaz Group, 2007) and its extended version, MIPVU (Steen et al., 2010) was employed. The revealed metaphors demonstrate that the pandemic in Georgia is mostly framed in terms of the WARFARE, JOURNEY and DISASTER super-scenarios, in Nerlich’s terms (Nerlich, 2011). In addition, the data show that the novel coronavirus may itself serve as a good source domain (Lakoff & Johnson, 198/2003; Grady, 1997, Kövecses, 2002; 2010) for political and societal issues: failures of the globalization, fear of foreigners and the future parliamentary election system in Georgia. Full Text (PDF)